Hypoglycaemic events resembling focal seizures -A case report and literature review. (January 2022) - Dudley, Alex; Khalil, Mohamed Ibrahim; Mullins, Gerard; Delanty, Norman; Naggar, Hany El
Highlights: Hypoglycaemic events can resemble focal seizures semiologically. Confirming the diagnosis by video EEG is important in drug resistant epilepsy. Insulinomas can lead to a misdiagnosis of epilepsy. Abstract: Purpose: To review the literature, for cases of hypoglycaemia misdiagnosed as epilepsy, including our interesting case of a patient with Type 1 Diabetes Mellitus, diagnosed with focal epilepsy. Methods: A literature search was completed. 20 of 473 studies, with a total of 22 cases found using specified search terms were relevant to this review. The papers identified and reviewed were those that dealt with hypoglycaemia misdiagnosed as epilepsy. The majority are isolated case reports given the rarity of this entity. Results: An underlying insulinoma is the most common cause for hypoglycaemic episodes to be misdiagnosed as epilepsy. Early morning seizures were prominent in 9 of the 22 cases. Conclusion: Although rare, hypoglycaemia is an important differential diagnosis for drug-resistant epilepsy and early morning events may be an indication. We report the first case of recurrent hypoglycaemia from exogenous insulin, misdiagnosed as focal epilepsy with an available video EEG. The unusual presentation appeared clinically indistinct from recurrent focal seizures.